KIERO (Kids Education Robot ) Educational Robot for Children's Learning Friends - Adi Nugraha; Diky Zakaria; Muchtar Ali Setyo Yudono (Fidelity : Jurnal Teknik Elektro, 2023)
The development of the child's brain at the age of 0-6 years is so rapid. At that time the child's brain development can reach 80% compared to adulthood. Therefore, a media is needed that can maximize the potential of children's brain development in the golden period which is adjusted to the times. In the era of Society 5.0 as it is now, it has become an important thing for us to prepare the next generation. In the era of Society 5.0, the use of IoT and robotics is very necessary, therefore a way is needed to provide an introduction to robotics and IoT from an early age to children. This can be done by creating robot-based learning media, not only training children's readiness, but this learning media is able to provide a great stimulus for children's motor development. With good motor development, of course, it can support cognitive development. The workings of a robot that uses RFID as an input center also provides a modern way of working, so that children are invited to learn a new way of working, this can invite them to hone their critical thinking, creative and problem solving skills